The Impact of Agricultural Land Use Patterns on Natural Vegetation, Plant, and Livestock Diversity in the European Union - Zsuzsanna Bacsi; Péter Szálteleki; Gabriella Bánhegyi (Heritage)
The preservation of natural heritage is a global concern nowadays, which is equally important for climate resilience and for sustainable resource use. The present research is focused on assessing the trends of natural landscape changes, such as forests, meadows, and pastures, and the preservation of locally kept traditional livestock, and plant varieties as indicators of biodiversity, in the countries of the European Union between 2012 and 2021, using secondary data. The research methodology was a panel analysis according to the Linear Mixed Model method. The results show that while larger areas allocated to agriculture generally enhance plant biodiversity, they have the opposite effect on the number of local livestock breeds. The spreading of organic farming enhances the preservation of local livestock breeds, while the spreading of forest areas is beneficial for plant biodiversity. The share of permanent meadows and pastures increases with increasing agricultural areas, and this also affects plant biodiversity positively. All biodiversity indicators increased during the analyzed period, as did well as the size of forest areas and, permanent meadows and pastures, which reflects the improvement in natural heritage and the enhancement of environmental protection awareness with time. The differences among countries show, that highly developed agriculture does not mean better preservation of natural heritage, nor the opposite, as ecological conditions and agricultural history may influence the natural vegetation and biodiversity. The protection of natural heritage in Europe differs from the rest of the world, as recent agricultural policy of the EU emphasizes the importance of environmental sustainability. The promotion of low-input use in agriculture, however, may be in conflict with the globally increasing demand for food.